Summary of Major Provisions of Senate Finance Committee Staff Option for Comprehensive Tax Reform [and Memo from Samuel D. Chilcote Jr. regarding excise taxes] - SAMUEL D. CHILCOTE JR. (Tufts Archival Research Center, 2007)
Marginalia; Missing Attachments; Memo from Samuel D. Chilcote to the Executive Committee attached to an analysis of Senator Packwood's tax reform bill. Labels the proposal as a "grave threat." Announces that the Tobacco Institute is stating its objections through spokesmen and at the grass roots level. Attached to summary of major provisions of the tax reform, with compliance and excise taxes sections highlighted.